A Syntactical Analysis of Christian Teaching According to James 1:16-27 - Chia, Philip Suciadi (Jurnal Didaskalia, 2024)
The book of James reveals three purposes of Christian’s tribulation. First, it comes from the present argument: let his endurance have a perfect result which is you become mature and complete, and lack of nothing (1:4). The second purpose derives from the future argument: blessed the one who endures in the tribulation. Because, after these things, he will receive the crown of life that God has promised to those who love Him (1:12). The last purpose uses the past argument: He gave us birth with his true word so that we might become the first fruit amongst his all creations. This article analyses the second and the last purpose through a syntactical analysis.